The p250GAP Gene Is Associated with Risk for Schizophrenia and Schizotypal Personality Traits - Ohi, Kazutaka; Hashimoto, Ryota; Nakazawa, Takanobu; Okada, Takeya; Yasuda, Yuka; Yamamori, Hidenaga; Fukumoto, Motoyuki; Umeda-Yano, Satomi; Iwase, Masao; Kazui, Hiroaki; Yamamoto, Tadashi; Kano, Masanobu; et al. (PloS one, 2012)
Hypofunction of the glutamate N-Methyl-d-aspartate (NMDA) receptor has been implicated in the pathophysiology of schizophrenia. p250GAP is a brain-enriched NMDA receptor-interacting RhoGAP. p250GAP is involved in spine morphology, and spine morphology has been shown to be altered in the post-mortem brains of patients with schizophrenia. Schizotypal personality disorder has a strong familial relationship with schizophrenia. Several susceptibility genes for schizophrenia have been related to schizotypal traits. We first investigated the association of eight linkage disequilibrium-tagging single-nucleotide polymorphisms (SNPs) that cover the p250GAP gene with schizophrenia in a Japanese sample of 431 schizophrenia patients and 572 controls. We then investigated the impact of the risk genetic variant in the p250GAP gene on schizotypal personality traits in 180 healthy subjects using the Schizotypal Personality Questionnaire. We found a significant difference in genotype frequency between the patients and the controls in rs2298599 (χ(2) = 17.6, p = 0.00015). The minor A/A genotype frequency of rs2298599 was higher in the patients (18%) than in the controls (9%) (χ(2) = 15.5, p = 0.000083). Moreover, we found that subjects with the rs2298599 risk A/A genotype, compared with G allele carriers, had higher scores of schizotypal traits (F(1,178) = 4.08, p = 0.045), particularly the interpersonal factor (F(1,178) = 5.85, p = 0.017). These results suggest that a genetic variation in the p250GAP gene might increase susceptibility not only for schizophrenia but also for schizotypal personality traits. We concluded that the p250GAP gene might be a new candidate gene for susceptibility to schizophrenia.